Physical activity for smoking cessation in pregnancy: randomised controlled trial - Ussher, Michael; Lewis, Sarah; Aveyard, Paul; Manyonda, Isaac; West, Robert; Lewis, Beth; Marcus, Bess; Riaz, Muhammad; Taylor, Adrian; Daley, Amanda; Coleman, Tim (BMJ Publishing Group Ltd., 2015)
Objective: To determine the effectiveness of a physical activity intervention for smoking cessation during pregnancy.